The Influence of Fear of Missing Out (FOMO) on Impulsive Purchasing Behavior of Premium Bus Company (PO) Tickets Among Bus Enthusiasts - Muhammad Rifqi Habibie; Ira Darmawanti (Journal of Educational Management Research, 2026)
The rapid growth of social media has transformed consumer purchasing behavior by increasing exposure to exclusive experiences and encouraging emotionally driven decision-making. In Indonesia's premium bus transportation sector, intensive digital interactions among members of the Bismania community may stimulate Fear of Missing Out (FoMO), leading to impulsive ticket purchases. This study aimed to examine the effect of FoMO on impulsive purchasing behavior toward premium bus tickets among Bismania members. A quantitative explanatory design was employed using purposive sampling, involving 164 respondents who completed a structured online questionnaire. Data were analyzed using descriptive statistics, validity and reliability tests, assumption testing, and simple linear regression. The results showed that FoMO has a positive and statistically significant effect on impulsive purchasing behavior (β = 1.060, p < 0.001), explaining 50.5% of the variance (R² = 0.505). These findings extend the application of the Stimulus–Organism–Response (S–O–R) theory to premium transportation services and demonstrate that FoMO is an important psychological determinant of impulsive purchasing. Practically, the findings provide guidance for premium bus operators to develop ethical and effective digital marketing strategies.